2022
DOI: 10.1101/2022.01.17.476513
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arresting microbiome development limits immune system maturation and resistance to infection

Abstract: Disruptions to the intestinal microbiome during weaning lead to long-term negative effects on host immune function. However, the critical host-microbe interactions occurring during weaning required for healthy immune system development remain poorly understood. We find that restricting microbiome maturation during weaning leads to stunted immune system development and increased susceptibility to enteric infection. We developed a gnotobiotic mouse model of the early-life microbiome designated as Pediatric Commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 63 publications
0
29
0
Order By: Relevance
“…Importantly, A. muciniphila was associated with lower risk of progression to T1D in the TEDDY trial 4 and murine studies implicated this microbe in decreasing T1D rates in NOD mice 15,16 ; however, the specific mechanisms by which it functions in NOD mice remain poorly understood. We determined that the ability of A. muciniphila to enhance RORγ + Foxp3 + Treg induction and commensal-targeting systemic antibody production are age restricted in NOD mice, with preweaning exposure to A. muciniphila being necessary for the microbe to modulate these immune responses in the context of a defined set of 9 bacteria that models the early-life microbiome 46 . Additionally, we demonstrated that the presence of A. muciniphila enhances antibody responses to Staphylococcus species in NOD mice colonized with PedsCom.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, A. muciniphila was associated with lower risk of progression to T1D in the TEDDY trial 4 and murine studies implicated this microbe in decreasing T1D rates in NOD mice 15,16 ; however, the specific mechanisms by which it functions in NOD mice remain poorly understood. We determined that the ability of A. muciniphila to enhance RORγ + Foxp3 + Treg induction and commensal-targeting systemic antibody production are age restricted in NOD mice, with preweaning exposure to A. muciniphila being necessary for the microbe to modulate these immune responses in the context of a defined set of 9 bacteria that models the early-life microbiome 46 . Additionally, we demonstrated that the presence of A. muciniphila enhances antibody responses to Staphylococcus species in NOD mice colonized with PedsCom.…”
Section: Resultsmentioning
confidence: 99%
“…The isolators were independently tested for contamination quarterly by Charles River Laboratories (NJ, USA). PedsCom NOD and C57BL/6J mice were generated as previously described 46 . Gnotobiotic mice were transferred sterilely to autoclaved cages containing the same bedding and food as isolator cages and housed outside isolators during experiments that required colonizing with A. muciniphila .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this germ-free environment also leads to significant impairment of immune system development and responses. For example, mice raised in sterile conditions develop higher levels of IgE and fail to induce the same levels of immune reactivity seen during the "weaning period" of wild-type mice (20)(21)(22)(23). This results in susceptibility to certain bacteria and increased risk of immunopathologies, complications which are not resolved with instillation of an "adult" or "wild-type" microbiome (21,22,24).…”
Section: Success and Limitations Of The Murine Modelmentioning
confidence: 99%
“…For example, mice raised in sterile conditions develop higher levels of IgE and fail to induce the same levels of immune reactivity seen during the "weaning period" of wild-type mice (20)(21)(22)(23). This results in susceptibility to certain bacteria and increased risk of immunopathologies, complications which are not resolved with instillation of an "adult" or "wild-type" microbiome (21,22,24). Additionally, mouse studies of the microbiome show a large genetic influence which is distinct from humans where <10% of taxa are thought to be heritable (24-28).…”
Section: Success and Limitations Of The Murine Modelmentioning
confidence: 99%